The Routledge companion to cultural history in the Western world
1 online resource
Keywords: The Routledge Companion to Cultural History in the Western World is a comprehensive examination of recent discussions and findings in the exciting field of cultural history. A synthesis of how the new cultural history has transformed the study of history, the volume is divided into three parts - medieval, early modern and modern - that emphasize the way people made sense of the world around them. Contributions cover such themes as material cultures of living, mobility and transport, cultural exchange and transfer, power and conflict, emotion and communication, and the history of the senses. The focus is on the Western world, but the notion of the West is a flexible one. In bringing together 36 authors from 15 countries, the book takes a wide geographical coverage, devoting continuous attention to global connections and the emerging trend of globalization. It builds a panorama of the transformation of Western identities, and the critical ramifications of that evolution from the Middle Ages to the twenty-first century, that offers the reader a wide-ranging illustration of the potentials of cultural history as a way of studying the past in a variety of times, spaces and aspects of human experience. Engaging with historiographical debate and covering a vast range of themes, periods and places, The Routledge Companion to Cultural History in the Western World is the ideal resource for cultural history students and scholars to understand and advance this dynamic field.